Polymer‐Supported Palladium(II) Carbene Complexes: Catalytic Activity, Recyclability, and Selectivity in C−H Acetoxylation of Arenes. Issue 35 (31st May 2017) - Majeed, Maitham H.; Shayesteh, Payam; Wallenberg, L. Reine; Persson, Axel R.; Johansson, Niclas; Ye, Lei; Schnadt, Joachim; Wendt, Ola F.
Abstract: Heterogeneous catalysts for selective oxidation of C−H bonds were synthesized by co‐polymerization of new N‐heterocyclic carbene‐palladium(II) (NHC‐Pd II ) monomers with divinylbenzene. The polymer‐supported NHC‐Pd II ‐catalysed undirected C−H acetoxylation of simple and methylated arenes as well as polyarenes, with similar or superior efficiency compared to their homogeneous analogues. In particular, the regioselectivity has been improved in the acetoxylation of biphenyl and naphthalene compared to the best homogeneous catalysts. The new polymer‐supported catalysts maintain the original oxidation state of Pd II after repeated catalytic reactions, and exhibit no significant leaching of palladium. In addition, the new catalysts have been successfully recovered and reused without loss of activity over several cycles of reactions. Abstract : Again and again : Co‐polymerization of divinyl benzene with vinyl moieties in a Pd II complex gives a recyclable heterogeneous catalyst that is active in direct acetoxylation of unactivated C−H bonds in arenes and where the selectivity is equal, and in some cases superior, to the corresponding homogenous catalysts.